Blockade of ERK1/2 activation with U0126 or PEP7 reduces sodium appetite and angiotensin II-induced pressor responses in spontaneously hypertensive rats - Andrade-Franzé, G. M.F. [UNESP]; Pereira, E. D. [UNESP]; Yosten, G. L.C.; Samson, W. K.; Menani, J. V. [UNESP]; De Luca, L. A. [UNESP]; Andrade, C. A.F. [UNESP] (Elsevier, 2021)
Spontaneously hypertensive rats (SHRs) have increased daily or induced sodium intake compared to normotensive rats. In normotensive rats, angiotensin II (ANG II)-induced sodium intake is blocked by the inactivation of p42/44 mitogen-activated protein kinase, also known as extracellular signal-regulated protein kinase1/2 (ERK1/2). Here we investigated if inhibition of ERK1/2 pathway centrally would change sodium appetite and intracerebroventricular (icv) ANG II-induced pressor response in SHRs. SHRs (280−330 g, n = 07–14/group) with stainless steel cannulas implanted in the lateral ventricle (LV) were used. Water and 0.3 M NaCl intake was induced by the treatment with the diuretic furosemide + captopril (angiotensin converting enzyme blocker) subcutaneously or 24 h of water deprivation (WD) followed by 2 h of partial rehydration with only water (PR). The blockade of ERK1/2 activation with icv injections of U0126 (MEK1/2 inhibitor, 2 mM; 2 μl) reduced 0.3 M NaCl intake induced by furosemide + captopril (5.0 ± 1.0, vs. vehicle: 7.3 ± 0.7 mL/120 min) or WD-PR– (4.6 ± 1.3, vs. vehicle: 10.3 ± 1.4 mL/120 min). PEP7 (selective inhibitor of AT1 receptor-mediated ERK1/2 activation, 2 nmol/2 μL) icv also reduced WD-PR-induced 0.3 M NaCl (2.8 ± 0.7, vs. vehicle: 6.8 ± 1.4 mL/120 min). WD-PR-induced water intake was also reduced by U0126 or PEP7. In addition, U0126 or PEP7 icv reduced the pressor response to icv ANG II. Therefore, the present results suggest that central AT1 receptor-mediated ERK1/2 activation is part of the mechanisms involved in sodium appetite and ANG II-induced pressor response in SHRs.
Keywords: Angiotensin II; Arterial pressure; Hypertension; Sodium appetite; Thirst